Gerakan Pemberdayaan Kesejahteraan Keluarga dalam Mewujudkan Kawasan Bebas Sampah - Oktavianus, Andre; Thamrin, Husni; Ritonga, Fajar Utama (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2023)
The Family Welfare Empowerment (PKK) movement is an important pillar in the effort to realize a waste-free area. Through a participatory and educative approach, PKK actively involves the community in waste prevention, reduction, and management efforts. This abstract explains the PKK's role in raising environmental awareness, promoting clean living behavior, and empowering families to practice concrete actions in household waste management. In this context, the abstract outlines the approaches adopted by the PKK, including extension campaigns, waste management training, and the establishment of joint working groups. Through the implementation of these programs, PKK seeks to create sustainable behavior change and build a clean, healthy and sustainable area. The evaluation results show that through active community involvement, PKK can successfully achieve the goal of realizing a waste-free area, which in turn will improve welfare and quality of life at the local level.